10 Jahre Galerie Michael Haas 1979-1989. - Galerie Michael Haas, Berlin (Berlin : Galerie Michael Haas, 1989)
Kirchner, Ernst Ludwig ; Mueller, Otto ; Dix, Otto ; Beckmann, Max ; Soutter, Louis ; Baumeister, Willi ; Fontana, Lucio ; Jorn, Asger ; Tàpies, Antoni ; Dubuffet, Jean ; Nay, Ernst Wilhelm ; Chaissac, Gaston ; Richter, Gerhard ; Kiefer, Anselm ; Rauschenberg, Robert ; Clemente, Francesco ; Basquiat, Jean Michel ; Paladino, Mimmo ; Baselitz, Georg
biografie
10 jahre Galerie Michael Haas : 1979-1989, Galerie Michael Haas, Berlin, Frühjahr 1989
boek